2001
DOI: 10.1081/jdi-100108195
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and Mineralocorticoids Influence on Extrarenal Potassium Metabolism in Chronic Hemodialysis Patients

Abstract: Insulin-mineral corticoids effects on extrarenal K+ metabolism in dialysis patients. During the inter-dialytic interval in dialyzed patients, hydrogen and potassium ions are regulated by extrarenal mechanisms. We studied the hormonal and acidotic effects on the extrarenal potassium metabolism, in selected, anuric and stable, hemodialysis patients. Fifteen patients, were grouped according to the mean mid-week pre-dialysis K+ over the past 12 months: > 6.0 mEq/L (G1, n=5), = 5.1-6.0 mEq/L (G2, n=5), < or = 5.0 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Mineralocorticoids (MC) induce a rise in arterial blood pressure. They have been proposed in the treatment of orthostatic hypotension and in hemodialysis patients, in the treatment of hyperkaliemia 3–6 and of per‐dialytic hypotension 7 . Some research was made about the safety of their use 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Mineralocorticoids (MC) induce a rise in arterial blood pressure. They have been proposed in the treatment of orthostatic hypotension and in hemodialysis patients, in the treatment of hyperkaliemia 3–6 and of per‐dialytic hypotension 7 . Some research was made about the safety of their use 7 .…”
Section: Introductionmentioning
confidence: 99%
“…However, increased extrarenal conservation of potassium in anuric ESRD patients has been seen with spironolactone doses of approximately 200 mg/d [32], and, likewise, with other studies in this population having employed daily spironolactone doses in the 300-to 400-mg range [31,33••].…”
Section: Aldosterone-receptor Antagonism In Hemodialysismentioning
confidence: 96%
“…Studies of Sugarman and Brown [23] in anephric humans receiving an oral potassium load after deoxycorticosterone or spironolactone treatment suggest that mineralocorticoid enhanced the removal of potassium from the extracellular space. However, relatively high doses of spironolactone were used in that study, as well as in the report of Vlassopoulus et al [24]. Recent trials have demonstrated the safety of low-dose spironolactone administration in chronic HD patients [25,26].…”
mentioning
confidence: 92%